2012
DOI: 10.1177/2040622312446007
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept in wet age-related macular degeneration: a perspective review

Abstract: In the treatment of neovascular age-related macular degeneration (AMD), vascular endothelial growth factor (VEGF) has emerged as a key target of therapy. Currently, patients with neovascular AMD are treated with monthly intravitreal injections of anti-VEGF medications. Aflibercept is a novel recombinant fusion protein engineered to bind all isoforms of VEGF-A, VEGF-B, and placental growth factor. It is the latest medication to receive US Federal Drug Administration (FDA) approval for the treatment of neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…50). Theoretical models suggested that this molecule may have a longer duration of action compared with current treatments (61). In recent phase 3 clinical trials, aflibercept, administered every second month after three monthly loading doses over 12 months, proved to be noninferior to monthly injections of ranibizumab, although with increased VEGF affinity, long-term follow-up for evaluation of neuronal degeneration is important (VIEW 1 and VIEW 2 studies, ref.…”
Section: Current Treatments Unmet Needs and Future Directionsmentioning
confidence: 99%
“…50). Theoretical models suggested that this molecule may have a longer duration of action compared with current treatments (61). In recent phase 3 clinical trials, aflibercept, administered every second month after three monthly loading doses over 12 months, proved to be noninferior to monthly injections of ranibizumab, although with increased VEGF affinity, long-term follow-up for evaluation of neuronal degeneration is important (VIEW 1 and VIEW 2 studies, ref.…”
Section: Current Treatments Unmet Needs and Future Directionsmentioning
confidence: 99%
“…Since it has been reported to have a substantially higher binding affinity for VEGF and a potentially longer duration of action in the eye than ranibizumab, aflibercept might, a priori, be predicted to be a potentially more effective treatment for AMD 15 16. In fact, in the VIEW ii studies, intravitreal aflibercept injections were as effective as ranibizumab in improving visual acuity in patients with AMD, but required fewer injections for the same effect 17.…”
Section: Introductionmentioning
confidence: 99%
“…Aflibercept (VEGF Trap-Eye, Eylea, Regeneron/Bayer) is a new anti-VEGF agent recently approved by the Food and Drug Administration. It is a fully human, recombinant fusion protein composed of the second immunoglobulin (Ig)-binding domain of VEGFR1 and the third Ig-binding domain of VEGFR2 fused to the fragment crystallisable (Fc) region of human IgG1 15. Aflibercept binds to all VEGF-A isoforms, VEGF-B and PlGF 11…”
Section: Introductionmentioning
confidence: 99%